2006
DOI: 10.1097/01.aog.0000222381.94325.4f
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-Releasing Hormone and Magnetic-Resonance–Guided Ultrasound Surgery for Uterine Leiomyomata

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 21 publications
0
68
0
5
Order By: Relevance
“…This finding is in line with the results of Hindley et al (3), which were a 13.5% fibroid volume reduction and a 27.3 point reduction in SSS at 6-month follow-up. Somewhat larger changes were reported in another study (16): Fibroid volume decreased by 21% at 6-month and by 37% at 12-month follow-up, while symptom severity was reduced by 45% at 6-month and 48% at 12-month follow-up. In this latter study, however, patients received a gonadotropin-releasing-hormone-agonist before sonication, which may have facilitated leiomyoma volume reduction by creating a temporary hypoestrogenic state.…”
Section: Discussionmentioning
confidence: 53%
“…This finding is in line with the results of Hindley et al (3), which were a 13.5% fibroid volume reduction and a 27.3 point reduction in SSS at 6-month follow-up. Somewhat larger changes were reported in another study (16): Fibroid volume decreased by 21% at 6-month and by 37% at 12-month follow-up, while symptom severity was reduced by 45% at 6-month and 48% at 12-month follow-up. In this latter study, however, patients received a gonadotropin-releasing-hormone-agonist before sonication, which may have facilitated leiomyoma volume reduction by creating a temporary hypoestrogenic state.…”
Section: Discussionmentioning
confidence: 53%
“…Current candidates for use as adjuncts include oxytocin infusion during the procedure as previously discussed, or preprocedure preparation with a course of gonadotropin-releasing hormone agonists, as has been shown to be effective in enhancing the effect of MRgFUS for leiomyomata. 48,49 UAE has been used with some success in the treatment of leiomyomata, and more recently has been used for the treatment of adenomyosis. Current UK National Institute for Health and Care Excellence guidance advises that UAE may be offered in the treatment of adenomyosis.…”
mentioning
confidence: 99%
“…Smart et al 10,11 have carried out research on the efficacy of HIFU combined with GnRHa for ablating uterine leiomyomas .10 cm in diameter. Compared with simple HIFU treatment, preliminary results from that study showed the use of a 3-month course of GnRHa therapy before HIFU improved the thermoablative treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…There was an average reduction in target leiomyoma volume of 21% and 37% at 6 months and 12 months. However, distinguished from Smart et al 10,11 study, this research focused on the uterine leiomyomas with homogeneous hyperintensity on T 2 weighted MRI-those with a diameter of 4-7 cm. A usual finding was the presence of degeneration inside fibroids .10 cm in diameter, and the research showed these leiomyomas manifested heterogeneous hyperintensity on T 2 weighted MRI and could be easily ablated by USgHIFU because they contained sparing cellularity and more fibres.…”
Section: Discussionmentioning
confidence: 99%